Expressway green belt maintenance drip irrigation pipeline and preparation method thereof

By using specific composite materials and preparation processes, a large-capacity highway green belt maintenance drip irrigation pipeline with excellent weather resistance, compressive strength, impact resistance, chemical stability and thermal expansion and contraction resistance was prepared, which solved the problems of short service life and frequent maintenance of existing pipelines and achieved more efficient maintenance results.

CN119823471AInactive Publication Date: 2025-04-15LIAONING TRANSPORTATION HIGHWAY TECH MAINTENANCE CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510309033.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing highway green belt maintenance drip irrigation pipelines have shortcomings in weather resistance, compressive strength, impact resistance, chemical stability and thermal expansion and contraction resistance, resulting in short service life and frequent maintenance.

Method used

Polyethylene, polypropylene, polybutene and other materials, combined with ethylene propylene ternary rubber, neoprene, aramid fiber and other components, through specific compounding ratios and preparation processes, a large-capacity highway green belt maintenance drip irrigation pipeline with good weather resistance, compressive strength, impact resistance, chemical stability and thermal expansion and contraction resistance are prepared.

Benefits of technology

It significantly improves the service life of the pipeline, reduces the maintenance and replacement frequency, enhances the weather resistance, compressive strength, impact resistance, chemical stability and thermal expansion and contraction resistance of the pipeline, and is suitable for the maintenance needs of highway green belts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to an expressway green belt maintenance drip irrigation pipeline and a preparation method thereof, and belongs to the technical field of high polymer materials. The pipeline is prepared from the following raw materials: polyethylene, polypropylene, polybutylene, ethylene propylene diene monomer, chloroprene rubber, aramid fiber, a methyl methacrylate-butadiene copolymer, phenolic resin, cetearyl alcohol polyoxyethylene ether, isomeric alcohol polyoxyethylene ether phosphate, a maleic anhydride grafted polymer, magnesium cordierite powder, silicon nitride powder and a plastic blending fusion agent. A hindered phenol antioxidant and the like; the magnesium cordierite powder is magnesium cordierite powder modified by gamma-aminopropyltriethoxysilane, and the magnesium cordierite powder is magnesium cordierite powder modified by gamma-aminopropyltriethoxysilane; the silicon nitride powder is silicon nitride powder modified by gamma-aminopropyl triethoxy silane. The components are compounded according to a specific ratio, and a specific preparation process method is combined, so that the prepared pipeline has good weather resistance, compressive strength, impact resistance, chemical stability and thermal expansion and cold contraction resistance, the service life of the pipeline can be prolonged, the pipeline is not easy to age and damage, and the maintenance and replacement frequency is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a highway green belt maintenance drip irrigation pipeline and a preparation method thereof. Background Art

[0002] With the rapid development of transportation, the construction of highways is constantly advancing. As an important part of the highway landscape and ecological environment, the maintenance of highway green belts has received increasing attention. Highway green belts are usually located in the median belt of highways, and their environmental conditions are relatively special. On the one hand, the dust and exhaust gas generated by vehicles on the highway will have an adverse effect on plant growth; on the other hand, the soil texture and fertility of highway green belts are often poor, and the ability to retain water and fertilizer is weak. In addition, due to the linear characteristics of highways, the length of green belts is long, the area is large, and irrigation is difficult.

[0003] In the early maintenance of highway green belts, people mainly used manual watering. This method is not only inefficient, but also difficult to ensure the uniformity and timeliness of watering, which can easily lead to poor plant growth or even death. With the advancement of technology, sprinkler irrigation systems have begun to be used in highway green belts. Although sprinkler irrigation can improve irrigation efficiency to a certain extent, there are problems such as low water resource utilization, susceptibility to wind, and easy to cause surface runoff and soil compaction. In order to solve these problems, drip irrigation technology has gradually been used in the maintenance of highway green belts.

[0004] As an advanced water-saving irrigation technology, drip irrigation technology has many advantages. First, drip irrigation can achieve precise irrigation, directly delivering water to the soil near the roots of plants, reducing water evaporation and leakage, and improving water resource utilization. Secondly, drip irrigation can carry out regular and quantitative irrigation according to the water demand of plants, ensuring that plants have sufficient water supply, which is conducive to plant growth and development. In addition, the drip irrigation system can also be combined with a fertilization device to achieve integrated water and fertilizer management, improve fertilizer utilization, and reduce environmental pollution.

[0005] However, the application of drip irrigation technology to the maintenance of highway green belts also faces some challenges. Due to the special environment of highway green belts, drip irrigation pipes need to have good weather resistance, pressure resistance and aging resistance to adapt to the complex outdoor climate conditions and the pressure caused by vehicle driving. Currently, the commonly used drip irrigation pipes for highway green belt maintenance are generally made of polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), etc., and there are the following problems: 1. Limited weather resistance: Long-term exposure to outdoor environments, subject to factors such as sunlight, temperature changes, and ultraviolet radiation, will gradually age and become brittle, reducing the service life of the pipeline.

[0006] 2. Relatively weak pressure resistance: In the highway environment, there will be vibration and pressure caused by driving vehicles. The pressure resistance of materials such as polyethylene and polypropylene is not enough to withstand these external forces, which can easily cause the pipeline to deform or even rupture.

[0007] 3. Insufficient impact resistance: When subjected to sudden external force impact, such as falling heavy objects or accidental vehicle collision, it may be damaged.

[0008] 4. Chemical stability needs to be improved: For some special chemicals, such as fuel, lubricating oil, deicing agent, snow removal agent, etc. that may exist on highways, the ability to resist chemical corrosion is relatively limited, which will affect the performance and life of the pipeline.

[0009] 5. Impact of thermal expansion and contraction: In an environment with large temperature changes, the thermal expansion and contraction of polyethylene and polypropylene are more obvious, which may cause the pipe connections to loosen or crack.

[0010] The above problems will affect the long-term stable operation and effect of drip irrigation pipes in the maintenance of highway green belts to a certain extent. Therefore, it is necessary to continuously develop and improve drip irrigation pipe technology to provide a safer and more reliable highway green belt maintenance drip irrigation system. Summary of the invention

[0011] Aiming at the problems of insufficient weather resistance, compressive strength, impact resistance and chemical stability, as well as large thermal expansion and contraction, in the existing drip irrigation pipelines for maintenance of green belts of highways. The present invention provides a drip irrigation pipeline for maintenance of green belts of highways and a preparation method thereof. The pipeline raw materials include polyethylene, polypropylene, polybutene, EPDM rubber, chloroprene rubber, aramid fiber, methyl methacrylate-butadiene copolymer, phenolic resin, cetearyl alcohol polyoxyethylene ether, isomeric alcohol polyoxyethylene ether phosphate, maleic anhydride grafted polymer, magnesium cordierite powder, silicon nitride powder, plastic blending agent, hindered phenol antioxidant, etc. The components are compounded in a specific proportion and combined with a specific preparation process. The prepared pipeline has good weather resistance, compressive strength, impact resistance, chemical stability and resistance to thermal expansion and contraction, can increase the service life of the pipeline, is not easy to age and damage, and effectively reduces the maintenance and replacement frequency. The specific technical scheme is as follows: A highway green belt maintenance drip irrigation pipeline, the pipeline is made of the following raw materials in parts by weight: 50 to 60 parts of polyethylene, 15 to 20 parts of polypropylene, 10 to 15 parts of polybutene, 10 to 15 parts of EPDM rubber, 8 to 10 parts of chloroprene rubber, 1 to 5 parts of aramid fiber, 1 to 5 parts of methyl methacrylate-butadiene copolymer, 3 to 5 parts of phenolic resin, 0.5 to 1.5 parts of cetearyl alcohol polyoxyethylene Vinyl ether, 2 to 5 parts of isomeric alcohol polyoxyethylene ether phosphate, 3 to 8 parts of maleic anhydride grafted polymer, 5 to 8 parts of magnesium cordierite powder, 2 to 5 parts of silicon nitride powder, 0.3 to 0.5 parts of plastic blending agent, 0.1 to 0.5 parts of hindered phenol antioxidant; wherein the magnesium cordierite powder is magnesium cordierite powder modified with γ-aminopropyltriethoxysilane; the silicon nitride powder is silicon nitride powder modified with γ-aminopropyltriethoxysilane.

[0012] Among the above ingredients, the maleic anhydride grafted polymer is EVA-g-MAH, and the model is 21E830.

[0013] Among the above ingredients, the model of isomeric alcohol polyoxyethylene ether phosphate is E-1310P.

[0014] Among the above ingredients, cetearyl alcohol polyoxyethylene ether is a flaky solid with a model number of O-60.

[0015] Among the above ingredients, the model of the plastic blending agent is HR-08.

[0016] Among the above ingredients, the model of the hindered phenol antioxidant is 1010.

[0017] Among the above ingredients, the phenolic resin is a powdered thermosetting phenolic resin.

[0018] In the above components, the aramid fiber has a diameter of 10 μm to 15 μm and a length of 1 mm to 3 mm.

[0019] Among the above components, the median particle size of the magnesium cordierite powder is less than 50 μm; the modification method of the magnesium cordierite powder includes the following steps: immersing the magnesium cordierite powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles under negative pressure, filtering, and obtaining magnesium cordierite powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0020] Among the above ingredients, the median particle size of the silicon nitride powder is less than 50 μm; the modification method of the silicon nitride powder includes the following steps: immersing the silicon nitride powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles under negative pressure, filtering, and obtaining silicon nitride powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0021] The above-mentioned method for preparing a drip irrigation pipeline for maintaining a highway green belt comprises the following steps: S1: Mixing magnesium cordierite powder and silicon nitride powder uniformly by air flow according to their mass fractions to obtain composite powder; immersing the composite powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles by negative pressure, filtering, and obtaining modified powder; S2: According to the mass proportions, EPDM rubber, chloroprene rubber, cetearyl alcohol polyoxyethylene ether and modified powder are plasticized at 60° C. to 100° C. for 20 min to 40 min to obtain a plasticized material; S3: Drying polyethylene, polypropylene and polybutylene to remove moisture; S4: Add polyethylene, polypropylene, polybutene, methyl methacrylate-butadiene copolymer, isomeric alcohol polyoxyethylene ether phosphate, plastic blending agent, and aramid fiber into an internal mixer according to their mass fractions, and perform internal mixing at 180°C to 200°C, at a speed of 30r / min to 50r / min, for 3min to 5min, and then add plasticizer, maleic anhydride grafted polymer, and phenolic resin, and perform internal mixing at 200°C to 250°C, at a speed of 60r / min to 80r / min, for 15min to 20min to obtain internal mixing material; S5: Use single-screw or twin-screw extruder for extrusion molding, air cooling and shaping.

[0022] In S3 of the above preparation method, the drying temperature is 80° C. to 120° C., and the drying time is 2 h to 4 h.

[0023] In S5 of the above preparation method, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 140°C to 150°C, the temperature of the compression zone is 220°C to 250°C, the temperature of the metering zone is 200°C to 220°C, and the temperature of the head zone is 180°C to 200°C; the extrusion speed of the extruder is 0.5m / min to 2m / min.

[0024] The invention provides a highway green belt maintenance drip irrigation pipeline and a preparation method thereof, which, compared with the prior art, has the following beneficial effects: 1. The raw materials of the pipeline of the present invention include polyethylene, polypropylene, polybutene, EPDM rubber, chloroprene rubber, aramid fiber, methyl methacrylate-butadiene copolymer, phenolic resin, cetearyl alcohol polyoxyethylene ether, isomeric alcohol polyoxyethylene ether phosphate, maleic anhydride grafted polymer, magnesium cordierite powder, silicon nitride powder, plastic blending agent, hindered phenol antioxidant, etc. The components are compounded in a specific proportion and combined with a specific preparation process. The prepared pipeline has good weather resistance, compressive strength, impact resistance, chemical stability and resistance to thermal expansion and contraction, can increase the service life of the pipeline, is not easy to age and damage, and effectively reduces the maintenance and replacement frequency; it is particularly suitable for drip irrigation pipelines for highway green belt maintenance.

[0025] 2. Magnesium cordierite powder can improve the strength and rigidity of the pipeline, better withstand internal pressure and external loads; can improve the dimensional stability of the pipeline, improve the installation accuracy and reliability of the pipeline, and has good resistance to thermal expansion and contraction, effectively preventing the joints from loosening or cracking, extending the service life of the pipeline, and reducing maintenance costs. Magnesium cordierite powder has a certain flame retardant effect, which can improve the flame retardant properties of the pipeline to a certain extent and reduce the risk of fire. Silicon nitride powder has high hardness and good wear resistance, which can improve the wear resistance of the pipeline; silicon nitride powder has good chemical stability and has strong resistance to corrosive media such as acids and alkalis. The combination of magnesium cordierite powder and silicon nitride powder helps to improve the weather resistance, compressive strength, impact resistance, chemical stability and resistance to thermal expansion and contraction of the pipeline.

[0026] 3. The present invention uses γ-aminopropyl triethoxysilane to modify the surface of magnesium cordierite powder and silicon nitride powder. On the one hand, it can improve the workability of magnesium cordierite powder, silicon nitride powder with EPDM rubber and chloroprene rubber, improve the fusion uniformity, reduce defects, and improve the strength, thermal expansion and contraction resistance of EPDM rubber and chloroprene rubber. On the other hand, γ-aminopropyl triethoxysilane can form a chemical bond at the interface between rubber and plastic, enhance the bonding force, and thus improve the quality of the pipeline. Moreover, γ-aminopropyl triethoxysilane has a better dispersion effect through the loading of magnesium cordierite powder and silicon nitride powder, which can reduce the amount of γ-aminopropyl triethoxysilane.

[0027] 4. The present invention is designed to immerse the composite powder of magnesium cordierite powder and silicon nitride powder in γ-aminopropyltriethoxysilane, stir and mix the immersion, and perform negative pressure bubble removal. The stirring, mixing and negative pressure bubble removal can well ensure that γ-aminopropyltriethoxysilane fully infiltrates the surface defects and pores of magnesium cordierite powder and silicon nitride powder, discharges gas, and effectively reduces the formation of pipeline bubbles in subsequent mixing and extrusion steps.

[0028] 5. Cetearyl alcohol polyoxyethylene ether can blend EPDM rubber, chloroprene rubber and modified powder well, improve plasticizing uniformity, improve material fluidity, prevent agglomeration, reduce defects and weak parts, and thus improve the quality and performance of plasticized materials. In addition, cetearyl alcohol polyoxyethylene ether also has certain weather resistance, UV resistance and oxidation resistance, which can improve the weather resistance of pipelines.

[0029] 6. The use of polyethylene, polypropylene and polybutene in a certain proportion can change the properties of plastics and combine the advantages of each material to make the composite plastic have good weather resistance, compressive strength, impact resistance, chemical stability and resistance to thermal expansion and contraction. Adding plastic blending agent to polyethylene, polypropylene and polybutene in the mixing process can greatly improve the binding of each component, and the plastic blending agent has good acid and alkali resistance.

[0030] 7. Methyl methacrylate-butadiene copolymer (MBS) plays an impact-resistant role and is a good impact-resistant additive; aramid fiber is a good toughening agent; phenolic resin is a crosslinking agent; isomeric alcohol polyoxyethylene ether phosphate is an antistatic softener; maleic anhydride grafted polymer plays a role in compatibility, toughening and coupling; hindered phenol antioxidant plays an anti-aging role. The combination of these components can well enhance the corresponding performance of the pipeline.

[0031] 8. The preparation method of the present invention pre-plasticizes EPDM rubber, chloroprene rubber, cetearyl alcohol polyoxyethylene ether, and modified powder, which can well fuse EPDM rubber and chloroprene rubber, and use the modified powder to modify the strength of the fusion of EPDM rubber and chloroprene rubber.

[0032] 9. The preparation method of the present invention pre-mixes polyethylene, polypropylene, polybutene, methyl methacrylate-butadiene copolymer, isomeric alcohol polyoxyethylene ether phosphate, plastic blending agent and aramid fiber in an internal mixer at 180°C to 200°C, which can well fuse polyethylene, polypropylene and polybutene, and obtain good toughness, impact resistance and antistatic properties without being disturbed by rubber components, making the fusion more uniform, thereby ensuring the subsequent fusion with the rubber components and ensuring the quality of pipeline preparation.

[0033] 10. The present invention designs the temperature range of the feed zone, compression zone, metering zone and head zone of the extruder according to the material characteristics, which can make the material fluidity moderate, prevent excessive melting or clogging of the feed port, and prevent overheating and decomposition of the material, thereby ensuring the extrusion density of the pipeline. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.

[0035] Example 1 A drip irrigation pipeline for maintaining a green belt of a highway, the pipeline being made of the following raw materials in parts by mass: 55 parts of polyethylene, 18 parts of polypropylene, 12 parts of polybutene, 12 parts of EPDM rubber, 9 parts of chloroprene rubber, 3 parts of aramid fiber, 3 parts of methyl methacrylate-butadiene copolymer, 4 parts of phenolic resin, 1 part of cetearyl alcohol polyoxyethylene ether, 3 parts of isomeric alcohol polyoxyethylene ether phosphate, 5 parts of maleic anhydride grafted polymer, 6 parts of magnesium cordierite powder, 3 parts of silicon nitride powder, 0.4 parts of plastic blending agent, and 0.3 parts of hindered phenol antioxidant.

[0036] Among them, the median particle size of the magnesium cordierite powder is 22μm, and the magnesium cordierite powder is magnesium cordierite powder modified with γ-aminopropyltriethoxysilane. The modification method includes the following steps: immersing the magnesium cordierite powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles with negative pressure, filtering, and obtaining magnesium cordierite powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0037] The median particle size of the silicon nitride powder is 18 μm, and the silicon nitride powder is silicon nitride powder modified with γ-aminopropyltriethoxysilane. The modification method comprises the following steps: immersing the silicon nitride powder in γ-aminopropyltriethoxysilane, stirring and mixing the powder, exhausting bubbles with negative pressure, filtering, and obtaining silicon nitride powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0038] The above-mentioned method for preparing a drip irrigation pipeline for maintaining a highway green belt comprises the following steps: S1: Magnesium cordierite powder and silicon nitride powder are mixed uniformly by air flow according to their mass fractions to obtain composite powder; according to the volume ratio, the composite powder:γ-aminopropyltriethoxysilane=1:3.5, the composite powder is immersed in γ-aminopropyltriethoxysilane, stirred and mixed at 55r / min for 12min, the bubbles are discharged by negative pressure, and the mixture is filtered until no liquid drips, to obtain a composite powder surface-modified by γ-aminopropyltriethoxysilane; S2: According to the mass proportions, EPDM rubber, chloroprene rubber, cetearyl alcohol polyoxyethylene ether and composite powder were plasticized at 80° C. for 30 min to obtain a plasticized material; S3: drying polyethylene, polypropylene and polybutylene at 100°C for 3h to remove moisture; S4: Add polyethylene, polypropylene, polybutene, methyl methacrylate-butadiene copolymer, isomeric alcohol polyoxyethylene ether phosphate, plastic blending agent, and aramid fiber into an internal mixer according to their mass fractions, and perform internal mixing at 190° C., a speed of 40 r / min, and a time of 4 min. Then, add plasticizer, maleic anhydride grafted polymer, and phenolic resin, and perform internal mixing at 230° C., a speed of 70 r / min, and a time of 18 min to obtain internal mixing material; S5: Use a single-screw or twin-screw extruder for extrusion molding, air cooling, and shaping; Among them, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 145°C, the temperature of the compression zone is 230°C, the temperature of the metering zone is 210°C, and the temperature of the head zone is 190°C; the extrusion speed of the extruder is 1m / min.

[0039] Example 2 A drip irrigation pipeline for maintaining a green belt of a highway, the pipeline being made of the following raw materials in parts by mass: 50 parts of polyethylene, 15 parts of polypropylene, 10 parts of polybutene, 10 parts of EPDM rubber, 8 parts of chloroprene rubber, 1 part of aramid fiber, 1 part of methyl methacrylate-butadiene copolymer, 3 parts of phenolic resin, 0.5 parts of cetearyl alcohol polyoxyethylene ether, 2 parts of isomeric alcohol polyoxyethylene ether phosphate, 3 parts of maleic anhydride grafted polymer, 5 parts of magnesium cordierite powder, 2 parts of silicon nitride powder, 0.3 parts of plastic blending agent, and 0.1 parts of hindered phenol antioxidant.

[0040] Among them, the median particle size of the magnesium cordierite powder is 5μm, the magnesium cordierite powder is magnesium cordierite powder modified by γ-aminopropyltriethoxysilane, and the modification method includes the following steps: immersing the magnesium cordierite powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles under negative pressure, filtering, and obtaining magnesium cordierite powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0041] The median particle size of the silicon nitride powder is 3 μm, and the silicon nitride powder is silicon nitride powder modified with γ-aminopropyltriethoxysilane. The modification method comprises the following steps: immersing the silicon nitride powder in γ-aminopropyltriethoxysilane, stirring and mixing the powder, exhausting bubbles with negative pressure, filtering, and obtaining silicon nitride powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0042] The above-mentioned method for preparing a drip irrigation pipeline for maintaining a highway green belt comprises the following steps: S1: Magnesium cordierite powder and silicon nitride powder are mixed uniformly by air flow according to their mass fractions to obtain composite powder; according to the volume ratio, the composite powder:γ-aminopropyltriethoxysilane=1:3, the composite powder is immersed in γ-aminopropyltriethoxysilane, stirred and mixed at 50r / min for 10min, the bubbles are discharged by negative pressure, and the mixture is filtered until no liquid drips, to obtain a composite powder surface-modified by γ-aminopropyltriethoxysilane; S2: According to the mass proportions, EPDM rubber, chloroprene rubber, cetearyl alcohol polyoxyethylene ether and composite powder were plasticized at 60° C. for 20 min to obtain a plasticized material; S3: Drying polyethylene, polypropylene and polybutylene at 80°C for 2h to remove moisture; S4: Add polyethylene, polypropylene, polybutene, methyl methacrylate-butadiene copolymer, isomeric alcohol polyoxyethylene ether phosphate, plastic blending agent, and aramid fiber into an internal mixer according to their mass fractions, and perform internal mixing at 180° C., a speed of 30 r / min, and a time of 3 min. Then, add plasticizer, maleic anhydride grafted polymer, and phenolic resin, and perform internal mixing at 200° C., a speed of 60 r / min, and a time of 15 min to obtain internal mixing material; S5: Use a single-screw or twin-screw extruder for extrusion molding, air cooling, and shaping; Among them, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 140°C, the temperature of the compression zone is 220°C, the temperature of the metering zone is 200°C, and the temperature of the head zone is 180°C; the extrusion speed of the extruder is 0.5m / min.

[0043] Example 3 A drip irrigation pipeline for maintaining a green belt of a highway, the pipeline being made of the following raw materials in parts by mass: 60 parts of polyethylene, 20 parts of polypropylene, 15 parts of polybutene, 15 parts of EPDM rubber, 10 parts of chloroprene rubber, 5 parts of aramid fiber, 5 parts of methyl methacrylate-butadiene copolymer, 5 parts of phenolic resin, 1.5 parts of cetearyl alcohol polyoxyethylene ether, 5 parts of isomeric alcohol polyoxyethylene ether phosphate, 8 parts of maleic anhydride grafted polymer, 8 parts of magnesium cordierite powder, 5 parts of silicon nitride powder, 0.5 parts of plastic blending agent, and 0.5 parts of hindered phenol antioxidant.

[0044] Among them, the median particle size of the magnesium cordierite powder is 48μm, and the magnesium cordierite powder is magnesium cordierite powder modified with γ-aminopropyltriethoxysilane. The modification method includes the following steps: immersing the magnesium cordierite powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles with negative pressure, filtering, and obtaining magnesium cordierite powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0045] Among them, the median particle size of the silicon nitride powder is 46μm, the silicon nitride powder is silicon nitride powder modified by γ-aminopropyltriethoxysilane, and the modification method includes the following steps: immersing the silicon nitride powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles under negative pressure, filtering, and obtaining silicon nitride powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0046] The above-mentioned method for preparing a drip irrigation pipeline for maintaining a highway green belt comprises the following steps: S1: Magnesium cordierite powder and silicon nitride powder are mixed uniformly by air flow according to their mass fractions to obtain composite powder; according to the volume ratio, the composite powder:γ-aminopropyltriethoxysilane=1:4, the composite powder is immersed in γ-aminopropyltriethoxysilane, stirred and mixed at 60r / min for 15min, the bubbles are discharged by negative pressure, and the mixture is filtered until no liquid drips, to obtain a composite powder surface-modified by γ-aminopropyltriethoxysilane; S2: According to the mass fractions, EPDM rubber, chloroprene rubber, cetearyl alcohol polyoxyethylene ether and composite powder were plasticized at 100° C. for 40 min to obtain a plasticized material; S3: Drying polyethylene, polypropylene and polybutylene at 120°C for 4 hours to remove moisture; S4: Add polyethylene, polypropylene, polybutene, methyl methacrylate-butadiene copolymer, isomeric alcohol polyoxyethylene ether phosphate, plastic blending agent, and aramid fiber into an internal mixer according to their mass fractions, and perform internal mixing at 200° C., a speed of 50 r / min, and a time of 5 min. Then, add plasticized material, maleic anhydride grafted polymer, and phenolic resin, and perform internal mixing at 250° C., a speed of 80 r / min, and a time of 20 min to obtain an internal mixing material; S5: Use a single-screw or twin-screw extruder for extrusion molding, air cooling, and shaping; Among them, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 150°C, the temperature of the compression zone is 250°C, the temperature of the metering zone is 220°C, and the temperature of the head zone is 200°C; the extrusion speed of the extruder is 2m / min.

[0047] Example 4 A drip irrigation pipeline for maintaining a green belt of a highway, the pipeline being made of the following raw materials in parts by mass: 50 parts of polyethylene, 20 parts of polypropylene, 10 parts of polybutene, 15 parts of EPDM rubber, 8 parts of chloroprene rubber, 5 parts of aramid fiber, 1 part of methyl methacrylate-butadiene copolymer, 5 parts of phenolic resin, 0.5 parts of cetearyl alcohol polyoxyethylene ether, 5 parts of isomeric alcohol polyoxyethylene ether phosphate, 3 parts of maleic anhydride grafted polymer, 8 parts of magnesium cordierite powder, 2 parts of silicon nitride powder, 0.5 parts of plastic blending agent, and 0.2 parts of hindered phenol antioxidant.

[0048] Among them, the median particle size of the magnesium cordierite powder is 16 μm, and the magnesium cordierite powder is magnesium cordierite powder modified with γ-aminopropyltriethoxysilane. The modification method includes the following steps: immersing the magnesium cordierite powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles with negative pressure, filtering, and obtaining magnesium cordierite powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0049] Among them, the median particle size of the silicon nitride powder is 32μm, the silicon nitride powder is silicon nitride powder modified by γ-aminopropyltriethoxysilane, and the modification method includes the following steps: immersing the silicon nitride powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles under negative pressure, filtering, and obtaining silicon nitride powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0050] The above-mentioned method for preparing a drip irrigation pipeline for maintaining a highway green belt comprises the following steps: S1: Magnesium cordierite powder and silicon nitride powder are mixed uniformly by air flow according to their mass fractions to obtain composite powder; according to the volume ratio, the composite powder:γ-aminopropyltriethoxysilane=1:3, the composite powder is immersed in γ-aminopropyltriethoxysilane, stirred and mixed at 60r / min for 10min, the bubbles are discharged by negative pressure, and the mixture is filtered until no liquid drips, to obtain a composite powder surface-modified by γ-aminopropyltriethoxysilane; S2: According to the mass fractions, EPDM rubber, chloroprene rubber, cetearyl alcohol polyoxyethylene ether and composite powder were plasticized at 100° C. for 20 min to obtain a plasticized material; S3: Drying polyethylene, polypropylene and polybutylene at 120°C for 2h to remove moisture; S4: Add polyethylene, polypropylene, polybutene, methyl methacrylate-butadiene copolymer, isomeric alcohol polyoxyethylene ether phosphate, plastic blending agent, and aramid fiber into an internal mixer according to their mass fractions, and perform internal mixing at 200° C., a speed of 30 r / min, and a time of 5 min. Then, add plasticizer, maleic anhydride grafted polymer, and phenolic resin, and perform internal mixing at 200° C., a speed of 80 r / min, and a time of 15 min to obtain internal mixing material; S5: Use a single-screw or twin-screw extruder for extrusion molding, air cooling, and shaping; Among them, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 150°C, the temperature of the compression zone is 240°C, the temperature of the metering zone is 220°C, and the temperature of the head zone is 200°C; the extrusion speed of the extruder is 0.8m / min.

[0051] Example 5 A drip irrigation pipeline for maintaining a green belt of a highway, the pipeline being made of the following raw materials in parts by mass: 60 parts of polyethylene, 15 parts of polypropylene, 15 parts of polybutene, 10 parts of EPDM rubber, 10 parts of chloroprene rubber, 1 part of aramid fiber, 5 parts of methyl methacrylate-butadiene copolymer, 3 parts of phenolic resin, 1.5 parts of cetearyl alcohol polyoxyethylene ether, 2 parts of isomeric alcohol polyoxyethylene ether phosphate, 8 parts of maleic anhydride grafted polymer, 5 parts of magnesium cordierite powder, 5 parts of silicon nitride powder, 0.3 parts of plastic blending agent, and 0.4 parts of hindered phenol antioxidant.

[0052] Among them, the median particle size of the magnesium cordierite powder is 27μm, the magnesium cordierite powder is magnesium cordierite powder modified with γ-aminopropyltriethoxysilane, and the modification method includes the following steps: immersing the magnesium cordierite powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles with negative pressure, filtering, and obtaining magnesium cordierite powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0053] The median particle size of the silicon nitride powder is 15 μm, and the silicon nitride powder is silicon nitride powder modified with γ-aminopropyltriethoxysilane. The modification method comprises the following steps: immersing the silicon nitride powder in γ-aminopropyltriethoxysilane, stirring and mixing the powder, exhausting bubbles with negative pressure, filtering, and obtaining silicon nitride powder with γ-aminopropyltriethoxysilane attached to the surface of the particles.

[0054] The above-mentioned method for preparing a drip irrigation pipeline for maintaining a highway green belt comprises the following steps: S1: Magnesium cordierite powder and silicon nitride powder are mixed uniformly by air flow according to their mass fractions to obtain composite powder; according to the volume ratio, the composite powder:γ-aminopropyltriethoxysilane=1:4, the composite powder is immersed in γ-aminopropyltriethoxysilane, stirred and mixed at 50r / min for 15min, the bubbles are discharged by negative pressure, and the mixture is filtered until no liquid drips, to obtain a composite powder surface-modified by γ-aminopropyltriethoxysilane; S2: According to the mass proportions, EPDM rubber, chloroprene rubber, cetearyl alcohol polyoxyethylene ether and composite powder were plasticized at 60° C. for 40 min to obtain a plasticized material; S3: Drying polyethylene, polypropylene and polybutylene at 80°C for 4 hours to remove moisture; S4: Add polyethylene, polypropylene, polybutene, methyl methacrylate-butadiene copolymer, isomeric alcohol polyoxyethylene ether phosphate, plastic blending agent, and aramid fiber into an internal mixer according to their mass fractions, and perform internal mixing at 180° C., a speed of 50 r / min, and a time of 3 min. Then, add plasticizer, maleic anhydride grafted polymer, and phenolic resin, and perform internal mixing at 250° C., a speed of 60 r / min, and a time of 20 min to obtain internal mixing material; S5: Use a single-screw or twin-screw extruder for extrusion molding, air cooling, and shaping; Among them, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 140°C, the temperature of the compression zone is 230°C, the temperature of the metering zone is 200°C, and the temperature of the head zone is 180°C; the extrusion speed of the extruder is 1.5m / min.

[0055] The maleic anhydride grafted polymer used in the above embodiments is EVA-g-MAH, model 21E830, Dongguan Sujia Polymer Raw Materials Co., Ltd.; the model of isomeric alcohol polyoxyethylene ether phosphate is E-1310P, Shanghai Huijun Chemical Co., Ltd.; cetearyl alcohol polyoxyethylene ether is a flaky solid, model O-60, Shaoxing Zhezao Chemical Co., Ltd.; the model of plastic blending agent is HR-08, Shanghai Hexin Fine Chemical Co., Ltd.; the model of hindered phenol antioxidant is 1010, Dongguan Dinghai Plastic Chemical Co., Ltd.; the phenolic resin is a powder thermosetting phenolic resin; the diameter of the aramid fiber is 10μm~15μm, and the length is 1mm~3mm. The model of polyethylene is 5000S, Daqing Petrochemical; the model of polypropylene is K8003, Sinopec; the polybutene is PB-1 polybutene, model P5250N; the model of EPDM rubber is 4045M, Suzhou Changyixin Plastic Chemical Co., Ltd.; the model of chloroprene rubber is CR2442, Shanghai Zhengshang Chemical Technology Co., Ltd.

[0056] Comparative Example 1 The magnesium cordierite powder and silicon nitride powder are not modified by soaking in γ-aminopropyltriethoxysilane; other parameters and methods are the same as in Example 1.

[0057] Comparative Example 2 No magnesium cordierite powder is added to the pipeline raw material; other parameters and methods are the same as in Example 1.

[0058] Comparative Example 3 No cetearyl alcohol polyoxyethylene ether is added to the pipeline raw material, that is, no cetearyl alcohol polyoxyethylene ether is added during rubber plasticization; other parameters and methods are the same as in Example 1.

[0059] Comparative Example 4 Magnesium cordierite powder, silicon nitride powder and cetearyl alcohol polyoxyethylene ether are not added to the pipeline raw material, that is, cetearyl alcohol polyoxyethylene ether and composite powder are not added during rubber plasticization; other parameters and methods are the same as in Example 1.

[0060] Comparative Example 5 No EPDM rubber, chloroprene rubber, or cetearyl alcohol polyoxyethylene ether is added to the pipeline raw material, that is, the composite powder directly replaces the plasticized material and is added to the internal mixer; other parameters and methods are the same as in Example 1.

[0061] Comparative Example 6 No isomeric alcohol polyoxyethylene ether phosphate is added to the pipeline raw material; other parameters and methods are the same as in Example 1.

[0062] Comparative Example 7 No plastic blending agent is added to the pipeline raw material; other parameters and methods are the same as in Example 1.

[0063] Comparative Example 8 No polypropylene, polybutene or plastic blending agent is added to the pipeline raw material; other parameters and methods are the same as in Example 1.

[0064] The following performance tests were performed on the pipes prepared in the above embodiments and comparative examples.

[0065] 1 Weathering test 1.1 Pipe sample specifications: pipe outer diameter 16mm, pipe inner diameter 12mm.

[0066] 1.2 Place the plastic pipe sample under standard environmental conditions (temperature 23°C, relative humidity 50%) for 24 hours to allow it to reach a stable state.

[0067] 1.3 Fix the treated plastic pipe sample on the sample rack of the xenon arc lamp aging test box to ensure that the sample surface can be evenly exposed to light for 30 days, with continuous light. Light intensity 0.55W / m² / nm (340nm); temperature: 50℃; humidity: 70%; spray water for 20 minutes every 5 hours.

[0068] 1.4 After 30 days, observe the color change (color difference is measured by colorimeter), surface cracks, powdering, blistering, etc.; then conduct hardness, tensile strength, and elongation at break tests, calculate the changes in hardness (Shore D-type hardness tester), tensile strength (universal material testing machine), and elongation at break (universal material testing machine) before and after the experiment, and evaluate the weather resistance. Change rate (reduction rate) = (value before the experiment - value after the experiment) / value before the experiment × 100%.

[0069] 1.5 Appearance evaluation level: 1-Excellent: The color change is minimal, and the color difference is less than or equal to 1.0; there are no defects such as cracks, powdering, blistering, etc. on the surface; 2-Good: Small color change, color difference greater than 1.0 and less than or equal to 2.0; only very slight cracks on the surface, no powdering; 3-Medium: The color change is obvious, the color difference is greater than 2.0 and less than or equal to 3.0; a small number of small cracks appear on the surface, but it does not affect the overall structural integrity; there is slight powdering; 4-Poor: Large color change, color difference greater than 3.0 and less than or equal to 4.0; obvious surface cracks and severe powdering; 5-Very Poor: The color changes greatly, with a color difference greater than 4.0; the surface is covered with cracks, and even partial peeling occurs; the powdering is serious, affecting the appearance and performance.

[0070] Three parallel samples were made for each test, and the average test results are shown in Table 1 below: Table 1 Weathering test results

[0071] It can be seen from the above results that the pipelines of Examples 1 to 5 have good weather resistance. From the comparison of the results of Comparative Example 1, it can be seen that the modification of magnesium cordierite powder and silicon nitride powder using γ-aminopropyl triethoxy silicon can promote the workability of magnesium cordierite powder and silicon nitride powder with other components, improve fusion uniformity, reduce defects, and γ-aminopropyl triethoxy silicon can form chemical bonds at the interface of rubber and plastic, enhance bonding force, and thus improve pipeline quality. After the weather resistance test, the performance decline is very small. From the comparison of the results of Comparative Example 2, it can be seen that magnesium cordierite powder has certain weather resistance, good heat resistance, and can improve the weather resistance of the pipeline. From the comparison of the results of Comparative Example 3, it can be seen that cetearyl alcohol polyoxyethylene ether can reconcile the uniformity of each component, improve material fluidity, prevent caking, reduce defects and weak parts, and cetearyl alcohol polyoxyethylene ether also has certain weather resistance, UV resistance, oxidation resistance, and can improve the weather resistance of the pipeline and reduce the performance change rate. As can be seen from the results of comparative example 4, magnesium cordierite powder, silicon nitride powder and cetearyl alcohol polyoxyethylene ether are used in combination, which has a good synergistic effect and can greatly improve the weather resistance of the pipeline. As can be seen from the results of comparative example 5, EPDM rubber, chloroprene rubber and cetearyl alcohol polyoxyethylene ether are used in combination, which has very excellent weather resistance and can greatly improve the weather resistance of the pipeline, especially the reduction effect of the change rate of tensile strength and elongation at break. As can be seen from the results of comparative example 6, isomeric alcohol polyoxyethylene ether phosphate can promote the quality improvement of the pipeline, thereby improving weather resistance. As can be seen from the results of comparative example 7, plastic blending agent can improve the fusion of polyethylene, polypropylene and polybutene, has good bonding, improves quality uniformity, and then improves weather resistance. As can be seen from the results of comparative example 8, polypropylene, polybutene and plastic blending agent are used in combination, which can change the properties of plastics, and well integrate the advantages of polyethylene, polypropylene and polybutene, and comprehensively improve weather resistance.

[0072] 2 Mechanical properties test 2.1 Pipe sample specifications: pipe outer diameter 16mm, pipe inner diameter 12mm.

[0073] 2.2 The compressive strength is tested by a pressure testing machine; 3 parallel samples are made for each type.

[0074] 2.3 Impact resistance is tested according to the drop hammer method of GB / T14152, with the drop hammer weight of 12kg, 14kg, and 16kg and the height of 2m. Ten specimens of each type are made and the number of cracks is counted.

[0075] Three parallel samples were made for each test, and the average test results are shown in Table 2 below: Table 2 Mechanical properties test results

[0076] It can be seen from the above results that the pipelines of Examples 1 to 5 have good compressive strength and impact resistance. From the comparison of the results of Comparative Example 1, it can be seen that the modification of magnesium cordierite powder and silicon nitride powder using γ-aminopropyl triethoxy silicon can affect the mechanical properties of the pipeline, γ-aminopropyl triethoxy silicon can improve the workability of magnesium cordierite powder and silicon nitride powder with rubber, improve the compressive strength of the rubber component, and γ-aminopropyl triethoxy silicon can form a chemical bond at the interface of rubber and plastic, enhance the bonding force, reduce defects, and thus improve the compressive strength and impact resistance of the pipeline. From the comparison of the results of Comparative Example 2, it can be seen that magnesium cordierite powder can well improve the mechanical properties of the pipeline. From the comparison of the results of Comparative Example 3, it can be seen that cetearyl alcohol polyoxyethylene ether can reconcile the uniformity of each component, improve material fluidity, prevent agglomeration, reduce defects and weak parts, reduce internal stress, and thus improve the mechanical properties of the pipeline. From the comparison of the results of comparative example 4, it can be seen that magnesium cordierite powder, silicon nitride powder and cetearyl alcohol polyoxyethylene ether are used in combination, which has a good synergistic effect and can greatly improve the mechanical properties of the pipeline. From the comparison of the results of comparative example 5, it can be seen that EPDM rubber, chloroprene rubber and cetearyl alcohol polyoxyethylene ether are used in combination to relieve impact force and greatly improve impact resistance. From the comparison of the results of comparative example 6, it can be seen that isomeric alcohol polyoxyethylene ether phosphate can promote the quality improvement of the pipeline, thereby improving certain mechanical properties. From the comparison of the results of comparative example 7, it can be seen that plastic blending agent can improve the fusion of polyethylene, polypropylene and polybutene, has good bonding, improves quality uniformity, reduces internal stress, and then improves mechanical properties. From the comparison of the results of comparative example 8, it can be seen that polypropylene, polybutene and plastic blending agent are used in combination to change the properties of plastics, and the advantages of polyethylene, polypropylene and polybutene are well integrated to comprehensively improve mechanical properties.

[0077] 3. Chemical stability test 3.1 Specifications of pipe specimens: outer diameter 16 mm, inner diameter 12 mm.

[0078] 3.2 Prepare the soaking solutions separately: 10% volume concentration of hydrochloric acid aqueous solution, 10% volume concentration of sulfuric acid aqueous solution, 10% mass concentration of sodium hydroxide aqueous solution, and 10% mass concentration of sodium chloride aqueous solution.

[0079] 3.3 After soaking for 48 hours, take out and wash with distilled water, dry, and observe the surface state of the pipe; then conduct hardness, tensile strength, and elongation at break tests, calculate the changes in hardness (Shore D hardness tester), tensile strength (universal material testing machine), and elongation at break (universal material testing machine) before and after the experiment, and evaluate weather resistance. Change rate (reduction rate) = (value before the experiment - value after the experiment) / value before the experiment × 100%.

[0080] 3.4 Performance test evaluation level: 1-No change: the change rate of hardness, tensile strength and elongation at break is less than or equal to 5%; 2- Slight decrease: The change rate of hardness, tensile strength and elongation at break is greater than 5% and less than or equal to 10%; 3-Moderate decrease: the change rate of hardness, tensile strength and elongation at break is greater than 10% and less than or equal to 20%; 4-Significant decrease: the change rate of hardness, tensile strength and elongation at break is greater than 20% and less than or equal to 30%; 5-Severe decline: The change rate of hardness, tensile strength and elongation at break is greater than 30%.

[0081] Three parallel samples were made for each test, and the average test results are shown in Table 3 below: Table 3 Chemical stability test results

[0082] It can be seen from the above results that the pipelines of Examples 1 to 5 have good resistance to acid and alkali corrosion. It can be seen from the results of Comparative Example 1 that the presence of a small amount of γ-aminopropyltriethoxysilane in the pipeline has little effect on the acid and alkali resistance of the pipeline. It can be seen from the results of Comparative Example 2 that the addition of magnesium cordierite powder can improve the tolerance of the pipeline to sulfuric acid. It can be seen from the results of Comparative Example 3 that the addition of cetearyl alcohol polyoxyethylene ether will affect the acid and alkali tolerance of the pipeline, and a small amount of addition will have little effect. It can be seen from the results of Comparative Example 4 that the absence of magnesium cordierite powder, silicon nitride powder and cetearyl alcohol polyoxyethylene ether in the pipeline raw materials will reduce the acid and alkali tolerance. It can be seen from the results of Comparative Example 5 that the absence of ethylene propylene diene rubber, chloroprene rubber and cetearyl alcohol polyoxyethylene ether in the pipeline raw materials will slightly affect the decrease in acid and alkali resistance. It can be seen from the results of Comparative Example 6 that the addition of isomeric alcohol polyoxyethylene ether phosphate will affect the alkali resistance, and a small amount of addition will have little effect. From the results of comparative example 7, it can be seen that the plastic blending agent helps to improve the acid and alkali resistance of the pipeline. From the results of comparative example 8, it can be seen that the combination of polypropylene, polybutylene and plastic blending agent can greatly improve the acid and alkali resistance of the pipeline.

[0083] 4 Thermal expansion and contraction test 4.1 Specifications of pipe specimens: outer diameter 16 mm, inner diameter 12 mm.

[0084] 4.2 Before the test, accurately measure the pipe diameter (the average value of the inner and outer diameters) at 25℃, which is the initial value D1; keep it warm at 60℃ and -40℃ for 2h respectively; take out the final value D2 (the average value of the inner and outer diameters) of the measured size, and calculate the thermal expansion coefficient and cold contraction coefficient.

[0085] Thermal expansion coefficient calculation formula: a=(D2-D1)÷[D1×(60-25)]; The calculation formula of cold shrinkage coefficient: b = (D1-D2) ÷ [D1× (25+40)]; The smaller the coefficient, the better the resistance to thermal expansion and contraction.

[0086] Three parallel samples were made for each test, and the average test results are shown in Table 4 below: Table 4 Thermal expansion and contraction test results

[0087] From the above results, it can be seen that the pipes of Examples 1 to 5 have good resistance to thermal expansion and contraction. From the results of Comparative Example 1, it can be seen that a small amount of γ-aminopropyltriethoxysilane in the pipe can improve the resistance to thermal expansion and contraction. From the results of Comparative Example 2, it can be seen that adding magnesium cordierite powder can improve the resistance to thermal expansion and contraction of the pipe.

[0088] It can be seen from the results of Comparative Example 3 that the addition of cetearyl alcohol polyoxyethylene ether can improve the pipe's resistance to thermal expansion and contraction.

[0089] It can be seen from the results of Comparative Example 4 that the addition of magnesium cordierite powder, silicon nitride powder and cetearyl alcohol polyoxyethylene ether will greatly improve the thermal expansion and contraction resistance of the pipeline. It can be seen from the results of Comparative Example 5 that the addition of EPDM rubber, chloroprene rubber, and cetearyl alcohol polyoxyethylene ether will affect the decline in the thermal expansion and contraction resistance of the pipeline, mainly due to the large thermal expansion and contraction coefficients of EPDM rubber and chloroprene rubber. It can be seen from the results of Comparative Example 6 that the addition of isomeric alcohol polyoxyethylene ether phosphate has little effect on the thermal expansion and contraction coefficient of the pipeline. It can be seen from the results of Comparative Example 7 that the plastic blending agent helps to improve the fusion of plastic components and improve the thermal expansion and contraction resistance of the pipeline. It can be seen from the results of Comparative Example 8 that the use of polypropylene, polybutene and plastic blending agents can improve the structure of the plastic components and enhance the thermal expansion and contraction resistance.

Claims

1. A drip irrigation pipeline for maintaining a highway green belt, characterized in that: The pipeline is made of the following raw materials in parts by mass: 50 to 60 parts of polyethylene, 15 to 20 parts of polypropylene, 10 to 15 parts of polybutene, 10 to 15 parts of ethylene-propylene rubber, 8 to 10 parts of chloroprene rubber, 1 to 5 parts of aramid fiber, 1 to 5 parts of methyl methacrylate-butadiene copolymer, 3 to 5 parts of phenolic resin, 0.5 to 1.5 parts of cetearyl alcohol polyoxyethylene ether, 2 to 5 parts of isomeric alcohol polyoxyethylene ether phosphate, 3 to 8 parts of maleic anhydride grafted polymer, 5 to 8 parts of magnesium cordierite powder, 2 to 5 parts of silicon nitride powder, 0.3 to 0.5 parts of plastic blending agent, and 0.1 to 0.5 parts of hindered phenol antioxidant; The magnesium cordierite powder is magnesium cordierite powder modified by γ-aminopropyltriethoxysilane; and the silicon nitride powder is silicon nitride powder modified by γ-aminopropyltriethoxysilane.

2. A highway green belt maintenance drip irrigation pipeline according to claim 1, characterized in that: The maleic anhydride grafted polymer is EVA-g-MAH, and the model is 21E830.

3. A highway green belt maintenance drip irrigation pipeline according to claim 1, characterized in that: The model of the isomeric alcohol polyoxyethylene ether phosphate is E-1310P.

4. A highway green belt maintenance drip irrigation pipeline according to claim 1, characterized in that: The cetearyl alcohol polyoxyethylene ether is a flaky solid with a model number of O-60.

5. A highway green belt maintenance drip irrigation pipeline according to claim 1, characterized in that: The model of the plastic blending agent is HR-08; the model of the hindered phenol antioxidant is 1010.

6. A highway green belt maintenance drip irrigation pipeline according to claim 1, characterized in that: The phenolic resin is a powdered thermosetting phenolic resin.

7. A highway green belt maintenance drip irrigation pipeline according to claim 1, characterized in that: The median particle size of the magnesium cordierite powder is less than 50 μm; the modification method of the magnesium cordierite powder comprises the following steps: immersing the magnesium cordierite powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting under negative pressure, filtering, and obtaining magnesium cordierite powder with γ-aminopropyltriethoxysilane attached to the particle surface.

8. A highway green belt maintenance drip irrigation pipeline according to claim 1, characterized in that: The median particle size of the silicon nitride powder is less than 50 μm; the modification method of the silicon nitride powder comprises the following steps: immersing the silicon nitride powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting under negative pressure, filtering, and obtaining silicon nitride powder with γ-aminopropyltriethoxysilane attached to the particle surface.

9. A method for preparing a highway green belt maintenance drip irrigation pipeline, used for preparing the highway green belt maintenance drip irrigation pipeline according to claim 1, characterized in that: The preparation method comprises the following steps: S1: Mixing magnesium cordierite powder and silicon nitride powder uniformly by air flow according to their mass fractions to obtain composite powder; immersing the composite powder in γ-aminopropyltriethoxysilane, stirring and mixing, immersing, exhausting bubbles by negative pressure, filtering, and obtaining modified powder; S2: According to the mass proportions, ethylene propylene rubber, chloroprene rubber, cetearyl alcohol polyoxyethylene ether and modified powder are plasticized at 60° C. to 100° C. for 20 min to 40 min to obtain a plasticized material; S3: Drying polyethylene, polypropylene and polybutylene to remove moisture; S4: Add polyethylene, polypropylene, polybutene, methyl methacrylate-butadiene copolymer, isomeric alcohol polyoxyethylene ether phosphate, plastic blending agent, and aramid fiber into an internal mixer according to their mass fractions, and perform internal mixing at 180°C to 200°C, at a speed of 30r / min to 50r / min, for 3min to 5min, and then add plasticizer, maleic anhydride grafted polymer, hindered phenol antioxidant, and phenolic resin, and perform internal mixing at 200°C to 250°C, at a speed of 60r / min to 80r / min, for 15min to 20min to obtain internal mixing material; S5: Use single-screw or twin-screw extruder for extrusion molding, air cooling and shaping.

10. The method for preparing a drip irrigation pipeline for maintaining a highway green belt according to claim 9, characterized in that: In S3, the drying temperature is 80℃~120℃, and the drying time is 2h~4h; in S5, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 140℃~150℃, the temperature of the compression zone is 220℃~250℃, the temperature of the metering zone is 200℃~220℃, and the temperature of the head zone is 180℃~200℃; the extrusion speed of the extruder is 0.5m / min~2m / min.

Citation Information

Patent Citations

  • Polyethylene corrugated pipe and preparation method thereof

    CN103937075A

  • Pipeline for laying wires and preparation method thereof

    CN106977788A

  • Environment-friendly polyolefin electricity material and preparation method of same

    CN107286417A

  • Anti-yellowing antibacterial polypropylene plastic for automobile decorations

    CN109181094A

  • Weather-resistant high-strength drainage pipe and preparation method thereof

    CN109796653A